Integrasi Teknologi (Telehealth, Web Based Intervention, Mobile health) Dalam Upaya Peningkatan Aktivitas Fisik Pasien Kanker - Hendra Dwi Cahyono; Dewi Irawaty (FORIKES, 2020)
Increased excess of cancer survivors by 70% in line with technological advances. Physical activity has an important role in improving cardiovascular function, muscle strength, immunity, fatigue, insomnia, and improving quality of life. Cancer rehabilitation programs in increasing patients to do physical activities that can be done in other ways between telehealth, email, web-based interventions and mobile health applications. The purpose of this literature study is to analyze the effectiveness of a new technology integrated in a rehabilitation program in an effort to increase physical activity in cancer patients. Literature search using the online database of EBSCOhost, Scopus, ScienceDirect, Cochrane, and Proquest, analyzed using CASP. There were 12 articles that met the inclusion criteria with a total of 1463 cancer patients. Almost all articles are related to the use of technology (telehealth, email, teleconference, web-based interventions, mobile health applications) in increasing the physical activity of cancer patients. There was a significant correlation between the increase in physical activity undertaken by patients and the improvement in the quality of life of cancer patients. Mobile health applications were one type of technology that is most easily accessed by patients compared to other types provided large information available, and communication with health workers. The patient’s condition and ability are impotant in developing technology in a cancer rehabilitation program, so that it was effective in increasing the physical activity of cancer patients Keywords: physical activity; mobilehealth; cancer rehabilitation program; technology ABSTRAK Peningkatan kuantitas penyintas kanker sebesar 70% seiring dengan kemajuan teknologi. Aktivitas fisik mempunyai peran penting meningkatkan fungsi kardiovaskular, kekuatan otot, imunitas, menurunkan nyeri, fatigue, insomnia, dan meningkatkan kualitas hidup. Program rehabilitasi pasien kanker dalam meningkatkan pasien untuk melakukan aktivitas fisik dapat dimodifikasi dengan banyak cara antara lain telehealth, email, web-based intervention dan mobile health application. Tujuan dari studi literatur ini untuk menganalisis keefektifan sebuah teknologi baru yang terintegrasi dalam sebuah program rehabilitasi sebagai upaya meningkatkan aktivitas fisik pada pasien kanker. Pencarian literature menggunakan online database EBSCOhost, Scopus, ScienceDirect, Cochrane, dan Proquest yang dianalisis menggunakan CASP. Terdapat 12 artikel yang memenuhi kriteria inklusi dengan total responden sebanyak 1463 pasien kanker. Hampir semua artikel menyebutkan adanya pengaruh yang signifikan penggunaan teknologi (telehealth, email, teleconference, web based intervention, mobile health application) dalam meningkatkan aktivitas fisik pasien kanker. Adanya korelasi yang signifikan antara peningkatan aktivitas fisik yang dilakukan pasien dengan peningkatan kualitas hidup pasien kanker. Mobile health application merupakan salah satu jenis teknologi yang paling disukai oleh pasien kanker dibandingkan dengan jenis yang lain dikarenakan kemudahan dalam mengakses informasi yang tersedia, serta kemudahan dalam berkomunikasi dengan tenaga kesehatan. Pentingnya kondisi dan kemampuan pasien dalam mengaplikasikan sebuah teknologi baru dalam suatu program rehabilitasi kanker sehingga pengembangan teknologi yang diaplikasikan tepat sasaran dan efektif dalam meningkatkan aktivitas fisik pasien kanker Kata kunci: aktivitas fisik; mobilehealth; program rehabilitasi kanker; teknologi